Deep dive exploring the real-world value of open source intelligence - Baker, Rae L (John Wiley & Sons, 2023)
Learn to gather and analyze publicly available data for your intelligence needs In Deep Dive: Exploring the Real-world Value of Open Source Intelligence, veteran open-source intelligence analyst Rae Baker explains how to use publicly available data to advance your investigative OSINT skills and how your adversaries are most likely to use publicly accessible data against you. The author delivers an authoritative introduction to the tradecraft utilized by open-source intelligence gathering specialists while offering real-life cases that highlight and underline the data collection and analysis processes and strategies you can implement immediately while hunting for open-source info. In addition to a wide breadth of essential OSINT subjects, you'll also find detailed discussions on ethics, traditional OSINT topics like subject intelligence, organizational intelligence, image analysis, and more niche topics like maritime and IOT. The book includes: Practical tips for new and intermediate analysts looking for concrete intelligence-gathering strategies Methods for data analysis and collection relevant to today's dynamic intelligence environment Tools for protecting your own data and information against bad actors and potential adversaries An essential resource for new intelligence analysts, Deep Dive: Exploring the Real-world Value of Open Source Intelligence is also a must-read for early-career and intermediate analysts, as well as intelligence teams seeking to improve the skills of their newest team members.